If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -42 + 11x = -7y Solving -42 + 11x = -7y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 11x = 42 + -7y Combine like terms: -42 + 42 = 0 0 + 11x = 42 + -7y 11x = 42 + -7y Divide each side by '11'. x = 3.818181818 + -0.6363636364y Simplifying x = 3.818181818 + -0.6363636364y
| 5.4x-8.3=14.8 | | 5X+2(x-1)=3x+4x+15 | | -2-3(4-4r)=-50 | | k/1.2=-0.07 | | .333y+11=.5y-3 | | x^2+6x+3=-6 | | 2.3(m)+m=26.4 | | 5=1.6x | | 5(3+5c)=60 | | 7b^2+32b+6=0 | | 57+x=6x+7 | | x^2+2x-101=2x-1 | | 16=c-(-12) | | -28+b=-7(b+4) | | 8k+6+5k=6 | | 8-3=n-13 | | 5d-25+2d=2d | | x+12=32-3x | | x^2+6x-32=2x | | 8-3=-13n | | 4y=24-0 | | x-4-9=0 | | 3X-7=10X+4-7X-11 | | 7(x-3)-(9x+2)=15 | | 10x-5(3x+5)=-10x | | 37-17=4(x-9) | | x^2+18x+75=-6 | | 7x=52 | | -2.1=d+(-9.3) | | 75+4v=150+1v | | 6(x-6)-10= | | a(b-2)=3a+b(a)-5a |